PEMBINAAN OLAHRAGA TINJU AMATIR DI SASANA DELTA BOXING CAMP KABUPATEN TEGAL DAN SASANA PERTINA KOTA TEGAL TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The background of this research there is a problem on the coaching done in Sasana and Tegal regency . The purpose of this study was to determine the amateur sport coaching in Boxing Camp Delta Sports Camps and Sports Camps Pertina Tegal Tegal in 2013 . This research uses qualitative research . The method used survey methods using techniques of observation , interview and documentation. The conclusions obtained are boxing coaching pattern implementation constraints. Organization has not been going well . Facilities and infrastructure need for the addition . Funding comes mostly from KONI . Training programs have been conducted in accordance with existing programs . Coach certified . Less than the maximum recruitment of athletes . Achievement is good enough